PENINGKATAN KESEHATAN PADA LANSIA MELALUI SENAM REMATIK UNTUK MENGATASI NYERI PENDERITA RHEUMATOID ARTHRITIS - Vera Fitriana; Hirza Ainin Nur; Luluk Cahyanti; Alvi Ratna Yuliana; Eny Pujiati; Jamaludin; Ambarwati; Icca Narayani Pramudaningsih (LPPM AN Nuur, 2024)
Background: Aging is associated with degenerative changes, one of the physical changes experienced by humans is changes in the musculoskeletal system, where the joint disorder that is often experienced by the elderly is rheumatoid arthritis (RA). The impact of rheumatism on the elderly is not only in the form of obvious limitations in mobility and daily living activities, the management that can be done to overcome this is doing physical activity with rheumatic exercises. Purpose: This community service aims to increase knowledge about exercise for the elderly with rheumatism among the community, especially the elderly at the Japanese village posyandu, Mejobo subdistrict. Method: implementing this community service activity is by providing health education and rheumatic exercise practices to the elderly. Activities start from the planning, implementation and evaluation stages of the results of the outreach activities. Results: The results of this activity show an increase in health knowledge in the elderly through rheumatic exercises to treat rheumatoid arthritis pain, which is indicated by the audience being able to answer questions about the material presented and being able to practice the rheumatic exercises taught. Conclusion: The results of this community service have proven effective in increasing understanding about improving health knowledge in the elderly through rheumatic exercises to treat rheumatoid arthritis (RA) painK